The fluctuating tense relief in German an analysis based on the pre- and post-temporal structures - Sadziński, Witold (Acta Universitatis Lodziensis. Folia Germanica, 2018)
The article follows on from Sadziński (2016) and is his “provocative” antithetical sequel. According to an internet research, sentences with even occasionally have no chronological order.The analysis carried out has shown that the sentence structures without time series mentioned often do ot understand themselves as temporal sentences.They are the result of de facto contamination with colloquially marked causal clauses.